Antipsychotic treatment of acute paranoid schizophrenia patients with olanzapine results in altered glycosylation of serum glycoproteins - Telford, Jayne E.; Leweke, F. Markus (Journal of proteome research, 2012)
Atypical antipsychotic drugs, such as olanzapine, have been shown to alleviate the positive, negative and, to a lesser degree, the cognitive symptoms of schizophrenia in many patients. However, the detailed mechanisms of action of these drugs have yet to be elucidated. We have carried out the first investigation aimed at evaluating the effects of olanzapine treatment on the glycosylation of serum proteins in schizophrenia patients. Olanzapine treatment resulted in increased levels of a disialylated biantennary glycan and reduced levels of a number of disialylated bi- and triantennary glycans on whole serum glycoproteins. These changes were not observed on a low-abundance serum protein fraction. α1 acid glycoprotein was identified as a carrier of some of the detected altered oligosaccharides. In addition, glycan analysis of haptoglobin, transferrin, and α1 antitrypsin reported similar findings, although these changes did not reach significance. Exoglycosidase digestion analysis showed that olanzapine treatment increased galactosylation and sialylation of whole serum proteins, suggesting increased activity of specific galactosyltransferases and increased availability of galactose residues for sialylation. Taken together, these findings indicate that olanzapine treatment results in altered glycosylation of serum proteins.
Gesehen am 13.06.2018